How does mistletoe infection affect seasonal physiological responses of hosts with different leaf phenology? - Scalon, Marina Corrêa; Rossatto, Davi Rodrigo [UNESP]; Franco, Augusto Cesar (Elsevier, 2021)
Plants should have the ability to perceive physiological changes within their branches when infected by mistletoes, adjusting the use of resources between infected and uninfected branches which can be crucial for their survival in the long-term. Here we investigated how branches infected by the mistletoe Passovia ovata (Pohl ex DC.) Tiegh. and uninfected branches within the same individual tree respond to seasonal environmental changes across two hosts of contrasting leaf phenology (the evergreen Miconia albicans (SW.) Triana and the deciduous Byrsonima verbascifolia (L.) DC.). We measured key leaf traits (instantaneous gas exchange rates, diurnal courses of stomatal conductance, leaf water potential, specific leaf area and leaf macronutrient concentrations) during the peak of the wet and dry season in a seasonal savanna of central Brazil. Pre-dawn leaf water potentials were consistently more negative for infected branches of both hosts, suggesting that overnight water refilling of infected branches was more limited. However, infected and uninfected branches exhibited similar leaf water potentials at midday, suggesting that they undergo similar imbalances in water supply and demand during periods of high atmospheric evaporative demand. Infected and non-infected branches of the evergreen mistletoe showed tighter regulation of water loss, whereas infected branches of the deciduous host were less constrained in regulating leaf transpiration. We also found differences for nutrient concentrations: N, P and K were lower, while Ca was higher in leaves of infected branches. Physiological changes induced by mistletoe infection affected host performance, and were reflected in water and nutrient use differences between infected and uninfected branches. Our findings show that infection responses by mistletoes can be detected between branches within individual trees, and that host species with distinct patterns of leaf phenology are capable to adjust, at the individual level, to cope with mistletoe's imposed physiological stress throughout the year.
Keywords: Cerrado; Gas exchange; Hemiparasite; Leaf phenology; Nutrients; Water use